The family creative workshop : costumes, crewelwork, crochet, decoupage, dioramas, dolls houses and furniture, dolls and dolls clothes dried flowers, dulcimers, egg decorating, embroidery - Bragdon, Allen Davenport (Plenary Publications International, 1975)
128 p. : il.; 27 cm.